Worsleyneset, Spitzbergen -- photograph ... - Seale, Linda N. (University of Alberta Library, 2008)
Worsleyneset at Lefdefjorden, north coast of Spitzbergen, Norway : gravel beaches surveyed in the early 20th century by Frank Worsley, later captain of Ernest Shackelton's ship 'Endurance' in the Antarctic. Photograph taken August 2008 ...